The production of critical thought in the Maghrib: Abdallah Laroui and Hichem Djaït (1965-1978) - Jebari, I (2015)
The critical essay gained immense popularity in the sixties and seventies in the Maghrib as a way to depict national realities that had failed to live up to nationalist ideals. Their authors often shared similar attributes: young highly educated intellectuals, committed toward modernity and who steered clear of politics. Such was the case of Abdallah Laroui (born 1933) and Hichem Djaït (born 1935), two celebrated Maghribi thinkers of the post-1967 generation in Arab thought. Despite their different ideological positions, they share a similar trajectory and both wrote about the need for another Arab renaissance, in Laroui's La crise des intellectuels arabes (1974) and Djaït's La personnalité arabo-islamique (1974). The turn to critical writing is routinely dismissed for being secondary, for having a restricted audience and little political impact, yet it highlights well the Maghribi postcolonial intellectual's competing demands: to conform to an ideal representation of intellectual "commitment" through critical speech, and to secure national recognition and integration. As such, this thesis confronts the often-neglected impact of nationalism on intellectual conducts after independence around the impact of their disillusionment, and forces us to rethink critically notions of engagement, the role of intellectuals and postcolonial cultural productions that are current in Middle East studies, and problematically envisaged by postcolonial studies. These texts have been approached as dynamic objects responding to a set of questions in their time, to account for the materiality of thought production, mobilising David Scott's concept of the "problem-space of intellectual production" (1999). This thesis looks at Abdallah Laroui and Hichem Djaït's intellectual projects from 1965 to 1978, to study the genesis and aftermaths of their critical moment, focusing on their published writings (critical essays and academic studies), press and journal articles, interviews, and fictional texts from a later period, in Arabic and French. Their writings will be read alongside several cultural journals, newspapers and memoirs dealing with this period of the Maghrib's history to account for the processes of circulation and reception by relevant audiences.